Influence of Information Needs and Information Seeking Behavior on Graduate School Students' Literacy Skills (British Journal of Multidisciplinary and Advanced Studies, 2024)
In today's intricate and swiftly changing information landscape, possessing information literacy skills is crucial for the academic endeavors of graduate school students. This study explored the influence of information needs and information seeking behavior of graduate school students on their information literacy skills. The research looked at how graduate students in a private higher education institution in Cagayan de Oro, during the first semester of the 2023-2024 school year, use and seek information. The study used a questionnaire answered by 347 participants from various courses. Findings show that the participants appeared a strong awareness of their information needs, indicating clarity in what they were looking for. They understood the importance of checking and confirming information to make sure it is reliable. The study also found that participants actively searched for information, considering their thoughts, feelings, and experiences in the process. Importantly, the participants demonstrated high skills in information literacy, including evaluating information, using effective search strategies, accessing online databases, and citing sources correctly. This suggests that they have a good understanding of key concepts related to information literacy and are proficient in using these skills. The study concluded that there is a significant connection between students' information needs, how they search for information, and their information literacy skills. Those who have higher information needs and actively seek information are more likely to have better information literacy skills. Overall, the research highlights the complex relationship between these factors in the academic environment.